A Creativity Education Model for Coastal Communities Amid the Covid-19 Pandemic - WASEHUDIN, Wasehudin; ANSHORI, Irfan; RAHMAN, M. Taufiq; SYAFE’I, Imam; KESUMA, Guntur Cahaya (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).12, 2021)
The Covid-19 Pandemic had a significant effect on the way people lived in western Java and how they got an education. This study is qualitative, and the subject of the study is the Tirtyasa community in Serang Regency, in the coastal area of Banten. This study illustrates the non-governmental organizations can influence and facilitate change in society. This research was conducted using a semi-structured interview. This article shows how we can exchange knowledge and experiences during the Covid-19 Outbreak. Company small business preparation can be achieved by good contact with colleagues and the use of appropriate technology.